Females of two species of Argia from Chapada dos Guimarães National Park, Brazil (Odonata: Coenagrionidae) - Vilela, Diogo Silva; Guillermo-Ferreira, Rhainer; Del-Claro, Kleber; Cordero-Rivera, Adolfo (Zootaxa, 2018)
The female of Argia tupi Calvert, 1909 (BRAZIL, Mato Grosso, Chapada dos Guimarães National Park, Cachoeira do Marimbondo (15.4330° S, 55.7198° W, 370 m), 01 xi 2015) is described, illustrated and diagnosed based on comparison with sympatric species of Argia Rambur, 1842. We also augmented the description of Argia bicellulata (Calvert, 1909) female (BRAZIL, Mato Grosso, Chapada dos Guimarães National Park, Rio Paciencia (15.3438° S, 55.8322° W, 280 m), 25 x 2015).